Lithium-lanthanum double chromates - Melnikov, P. [UNESP] (Elsevier, 1993)
Synthesis and crystallographic data are reported for low and high temperature forms of LiLa(CrO4)2. The compounds are closely related to lamellar rare earth phosphates and arsenates of sodium and to RbLu(CrO4)2. Lattice parameters of the orthorhombic (low temperature) and monoclinic (high temperature) forms are given. The low temperature form is moisture sensitive and Li+ ions are easily displaced by protons. Thermal decomposition takes place at 250 °C and results in the formation of LiCrO2, LaCrO4, LaCrO3 and Cr2O3. © 1993.
Keywords: Crystal lattices; Crystallography; Ionic conduction in solids; Lanthanum compounds; Lithium compounds; Pyrolysis; Synthesis (chemical); Lithium lanthanum double chromates; Monoclinic lattice parameters; Orthorhombic lattice parameters; Chromates